Physicochemical and Sensory Properties of Ginger Spiced Yoghurt - Moyouwou Amadou, Njoya; Abah Richard, Ejoh; Caroline Waingeh, Nain; Hélène, Imele; Kelly Ndombow, Yakum; Jules-Roger, Kuiate (Journal of Nutritional Therapeutics, 2017)
The physicochemical and sensory properties of ginger spiced yoghurt were investigated in the present study. Four yoghurt samples: A, B, C and D were prepared by addition of 0, 0.5, 1 and 1.5% (W/V) of ginger powder. Physicochemical properties of yoghurt samples determined at day 0 included pH, titratable acidity, dry matter, ash, fat and non-fat solid (NFS). The pH and titratable acidity were also evaluated during 30 days of storage at refrigerated conditions (4 – 6°C). The sensory attributes assessed were colour, odour, taste, texture and overall acceptability. From the results, ginger powder did not affect (P>0.05) the pH and titratable acidity of yoghurt but increased (P≤0.05) the dry matter, fat, NFS and ash content especially when spiced at 1% and 1.5% level. The spiced yoghurt did not show significant changes (P>0.05) in titratable acidity during storage as opposed to the unspiced yoghurt that increased (P<0.05) with storage time. The pH values of spiced yoghurt were not significantly affected (P>0.05) by storage contrary to the unspiced yoghurt. At the end of storage, the unspiced yoghurt presented the lowest (P≤0.05) pH and the highest (P≤0.05) titratable acidity. Results of sensory evaluation revealed the low appreciation of the spiced yoghurt with an increase in the proportion of ginger powder. However, yoghurt with 0.5% ginger powder was appreciated equally (P>0.05) with the unspiced sample. Spicing yoghurt with ginger powder therefore has positive effect on its physicochemical properties and shelf –life. The yoghurt spiced with 0.5% ginger powder could therefore be recommended.